Rancang Bangun Alat Ukur Lemak Tubuh Menggunakan Metode Bioelectrical Impedance Analysis - Sulistyo, Eko; Hermawan, Anissa Putri Aprilia; Ramadhan, Ikhram Pratama; Yudhi, Yudhi (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Many people in general still use manual weight measurement, even though manual weight measurement cannot distinguish between fat mass and non-fat mass. Therefore, in this study, the authors created a tool that can measure body fat percentage using the Bioelectrical Impedance Analysis (BIA) method. The BIA method is a method of measuring body fat levels by sending an AC current at a certain frequency to the body. Then by measuring the voltage generated, it can be known the magnitude of the impedance value in the human body. In measuring fat, the authors chose the hand-to-hand method. Starting from generating an AC signal with a frequency of 50kHz by the Oscillator circuit, it is then processed by the Howland circuit so that the current sent to the body is constant with a value of 0.22mA. This tool uses a load cell sensor as a body weight detector and an ultrasonic sensor as a body height detector. By using these tools the user can determine the value of body weight and height as well as the percentage of body fat with an accuracy of up to 96.22% when compared to Omron products, whereas when compared to manual measurements without methods, the average accuracy value is 82.23%. From this comparison, it can be concluded that fat measurement using the BIA method is more accurate than manual fat measurement.